Good Corporate Governance (GCG) pada Usaha Kecil dan Menengah (UKM) : Tinjauan Literatur Sistematis tentang Kinerja Keuangan, Keberlanjutan ESG, Ketahanan Bisnis,dan Inovasi - Yus Djunaedi Rusli; Herry Achmad Buchory; Dede Sugandi; Hasti Pramesti Kusnara (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study presents a Systematic Literature Review (SLR) aimed at mapping and synthesizing empirical evidence on the role of Good Corporate Governance (GCG) in Small and Medium Enterprises (SMEs) across both developing and developed countries. Addressing five core research questions, this review examines: (1) the influence of GCG on SME financial performance; (2) the contribution of ESG principles to SME sustainability amid global disruptions; (3) the moderating role of GCG on SME business continuity during crises; (4) the level of GCG implementation in Indonesian SMEs; and (5) the use of disruptive digital innovation to strengthen GCG and reduce corruption. A total of 20 articles sourced from the Semantic Scholar database and published between 2020 and 2026 were analyzed using the PRISMA protocol. Findings consistently indicate that GCG positively impacts SME financial performance, although this relationship is contextual and depends on profitability levels and interactions among governance mechanisms. ESG adoption enhances SME sustainability and reduces leverage manipulation, while robust GCG significantly moderates the negative effects of external crises such as the COVID-19 pandemic.